Adsorption and Kinetic Studies Of A Natural Dye from Curcuma longa L., Onto Bamboo Yarn - Tengku Khamanur Azma, Tg. Mohd Zamri; Mimi Sakinah, A. M.; Zularisam, A. W. (Universiti Malaysia Pahang, 2017)
Natural dye extracted from the rhizome of Curcuma longa L. were applied to bamboo yarns using exhaustion dyeing process. This study investigates the dyeing behaviour of Curcumin; the major color component isolated from rhizomes of Curcuma longa L. on bamboo yarn. Langmuir, Freundlich, Tempkin and Dubinin-Radushkevich isotherm models were used to test the adsorption process of curcumin on bamboo yarn. Comparison of regression coefficient value indicated that the Freundlich isotherm most fitted to the adsorption of curcumin onto bamboo yarn. Furthermore, the kinetics study on this research fitted the pseudo-second order model which indicates that the basis of interaction was chemical adsorption.